HOME GARDEN VALUE IN ISLAMIC PERSPECTIVE FOR RURAL DEVELOPMENT IN SITU UDIK BOGOR - Endin Mujahidin; Bahagia Bahagia; Fachruddin Majeri Mangunjaya; Rimun Wibowo (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
The objective of this research was to investigate home garden value for rural development in Situ Udik Bogor West Java. The research method used ethnographic qualitative approach. This method was related to community, social and environment. The data were collected through in-depth interviews, observation, and documentation. The selection of sample as informant exert purposive sampling technique. The result was probed meticulously through triangulation technique. The result showed that chief of village play imperative role to flourish rural community for program namely one banana trees in each home garden of society. The other was the home gardening impact on economic value. Society in the village can gain numerous merits of one banana trees which is cultivated in yard including community can exert outcome of banana yield for paying property taxes, add household income and allocate for school fee children. The other is to release ecology value. Home gardening has some function including protecting water from the surface flow and avoids environment from flooding disaster, reducing emission which is caused by global warming or climate change, produce oxygen and safeguard of soil fertility. Islam pledge to the person who conserves the natural environment like cultivating trees refers to produce alms and worship.